2017
DOI: 10.3389/fnbeh.2017.00206
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Time and Space: States of High Arousal Disrupt Implicit Acquisition of Spatial and Sequential Context Information

Abstract: Biased cognition during high arousal states is a relevant phenomenon in a variety of topics: from the development of post-traumatic stress disorders or stress-triggered addictive behaviors to forensic considerations regarding crimes of passion. Recent evidence indicates that arousal modulates the engagement of a hippocampus-based “cognitive” system in favor of a striatum-based “habit” system in learning and memory, promoting a switch from flexible, contextualized to more rigid, reflexive responses. Existing fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 145 publications
(206 reference statements)
0
17
0
Order By: Relevance
“…Given that orexins promote arousal, and changes in arousal can modulate cognitive function (Maran et al, 2017; Packard and Goodman, 2012), these neuropeptides likely play an important role in cognition. In support of this, narcoleptic patients show specific cognitive impairments (Blackwell et al, 2017).…”
Section: Orexins and Phenotypes Relevant To Mental Healthmentioning
confidence: 99%
“…Given that orexins promote arousal, and changes in arousal can modulate cognitive function (Maran et al, 2017; Packard and Goodman, 2012), these neuropeptides likely play an important role in cognition. In support of this, narcoleptic patients show specific cognitive impairments (Blackwell et al, 2017).…”
Section: Orexins and Phenotypes Relevant To Mental Healthmentioning
confidence: 99%
“…The fluctuations of arousal within active wake states have been assessed by measuring baseline pupil size, a surrogate measure of arousal. Such studies have shown that baseline pupil size allows distinguishing active task solving versus mind wandering (Kristjansson et al, 2009;Smallwood et al, 2011;Unsworth & Robison, 2016van den Brink et al, 2016a), exploitation versus exploration states (Jepma & Nieuwenhuis, 2011;Murphy et al, 2011;Pajkossy et al, 2017), focused attention versus fatigue (Nishiyama et al, 2007) or stress (Maran et al, 2017), all of which may alternate even during the course of a task. In addition to studies in humans, animal studies have shown that states associated with different level of arousal during the wake state show different pupil signatures, as well as different signatures of activity at the neuronal level.…”
Section: Introductionmentioning
confidence: 99%
“…First, like event boundaries, emotional stimuli or acute stressors that induce arousal elicit exaggerated estimates of time duration [23,24]. Second, viewing highly arousing videos prior to navigation or sequence learning has been shown to impair temporal order memory for neutral events [25][26][27]. Third, emotionally arousing stimuli also enhance local item-context source memory, at least when attention is directed towards relevant contextual information or when these details are intrinsic to the emotional stimulus [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%